News with an attitude ideological perspectives in the historical press - Claridge, Claudia 1965- (John Benjamins Publishing Company, 2025)
"This volume extends research on ideology in the news into the historical sphere, spanning discourse from the mid-seventeenth to the early twentieth century. The chapters investigate the ideological representation and assessment of political events across three continents, such as uprisings, independence, and genocide, but also of pervasive socio-cultural aspects like gender and language. For this, they rely on a wide range of sources, from handwritten news letters via general daily papers to specialized magazines, and from classical editorial content to letters published in newspapers. The geographical and linguistic focus of the texts investigated comprises British, American, Italian, German, and Polish discourse. The articles use both qualitative and quantitative corpus-based methodology, such as keyword or collocational analysis. The book is of interest for scholars in (historical) linguistics, history, and journalism studies"--
Keywords: Geschichte 1650-1926; Zeitung; Ideologie; Deutschland; USA; Großbritannien; Italien; Polen; Journalism / History; Journalism / Language; Mass media and language; Journalisme / Histoire; Journalisme / Langage; Médias et langage; Konferenzschrift -- 2022 -- Augsburg